Effectiveness of Global Postural Re-education for Treatment of Spinal Disorders: A Meta-analysis. (February 2017) - Lomas-Vega, Rafael; Garrido-Jaut, María Victoria; Rus, Alma; del-Pino-Casado, Rafael
Abstract : Objective: The aim of this study was to investigate the effects of global postural re-education (GPR) on the treatment of spinal disorders by performing a systematic review and a meta-analysis. Design: MEDLINE, Scopus, and PEDro databases were searched without language or publication date restrictions. Data on pain and function were used to evaluate the effectiveness of GPR. Randomized controlled trials and controlled clinical trials analyzing the effectiveness of GPR on spinal disorders were selected. The standardized mean difference (SMD) and the corresponding 95% confidence interval (95% CI) were calculated. The meta-analysis was performed using the Comprehensive Meta-analysis 3.3 software. Results: Seven randomized controlled trials and 4 controlled clinical trials were included in the meta-analysis. The results showed a medium improvement on pain (SMD = −0.63; 95% CI, −0.43 to −0.83) and function (SMD = −0.48; 95% CI, −0.25 to −0.72) after GPR treatment. The positive effect, which was greater in patients with ankylosing spondylitis followed by low back pain and neck pain, was more significant during the intermediate follow-up than immediately after treatment. Conclusions: This meta-analysis provides reliable evidence that GPR may be an effective method for treating spinal disorders by decreasing pain and improving function. Abstract : Supplemental digital content is available in the text.